Harmonic analysis of high penetration of solar rooftop system in an unbalanced EV loading distribution network - Phuriphat Samphanthasit; Weerakorn Ongsakul; Singh, Jai Govind; Than Lin; PEA; Asian Institute of Technology Education Cooperation Project; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2018)
So far, solar rooftop photovoltaic (PV) in Thailand have been widely used to supply power in residential and commercial buildings. Electric vehicle (EV) usage is expected to grow very fast in the upcoming years. The power system is expected to face huge challenges of the high penetration of single phase EV charging, single phase and three phase solar rooftop PV in residential area. Although high penetration of solar rooftop PV system and EV loading have advantages on fossil fuel consumption and CO2emission reduction, it will lead to low power system quality including voltage unbalance and harmonic in distribution system. This thesis proposes harmonic analysis of high penetration of solar rooftop system in an unbalanced EV loading distribution network. The test system includes 288 houses in residential unbalanced distribution network with high penetration three phase solar rooftop PV and single phase EV load. A voltage unbalance occurs when single phase EV load is connected to only one phase of the distribution system. A harmonic is injected into the network through non-linear three phase PV inverter. The simulation is done on Digsilent Power factory. Firstly, the voltage unbalanced levels are investigated with the maximum penetration of single phase EV load and single phase solar rooftop PV in residential distribution system. Secondly, the harmonic distortion levels are investigated with a high penetration of three phase solar rooftop on residential balanced and unbalanced distribution system. Finally, the mitigation techniques to reduce the voltage unbalance and total harmonic distribution voltage (THDV) on unbalanced distribution system are recommended. Simulation results indicate that for voltage unbalanced study, either the single phase EV penetration maximum limit of 43.79% or the single phase solar rooftop PV maximum penetration limit of 46.34% rooftop PV will not cause voltage unbalance to exceed 2% limit. However, only the single phase EV penetration maximum limit of 25.61% and single phase(connected at different phase)solar rooftop PV maximum limit of 25.61% will not cause voltage unbalance to exceed 2%limit. For harmonic distortion analysis, three phase solar rooftop PV maximum penetration limit of 8.15% will not cause THDV to exceed 5% limit on both balanced and unbalanced distribution systems. For mitigation techniques, energy storage of 2 MW effectively increases the single phase EV penetration maximum limit from 43.79% to 56.88%. Connecting filters at all PCC, double tuned type-3 harmonics filters effectively increase the penetration maximum limit of three phase solar rooftop PV from 8.15% to 66.51% and 62.68% in the balanced and unbalanced distribution network, respectively. For a combination of two filters installation, single tuned and double tuned type 4at main substation PCC effectively increases the penetration maximum limit of three phase solar rooftop PV from 8.14% to 67.39% on the unbalanced distribution system. In conclusion, the maximum penetration limit of three phase solar rooftop will decrease when voltage unbalance increases.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Energy
Thesis (M.Eng.) - Asian Institute of Technology, 2018
Keywords: Photovoltaic power systems; Electric vehicles -- Power supply